A prática do ensino de Filosofia e sua relação com as matrizes referenciais do Exame Nacional do Ensino Médio (ENEM) - Sousa, Luiz Fernando Borges de (2019)
This research aims to approximate the practice of the Philosophy teacher in the classroom with the official reference matrices that give rise to the National High School Exam - ENEM, as well as to understand analytically the items presented in this exam, as a fundamental opportunity to improve the its didactics and its evaluation method. Considering the formal and pedagogical requirements of teaching Philosophy, without losing the specificity of philosophical knowledge, is also the intention of the present work. In this perspective, ENEM is a possible conditional means for the philosophical act, which is the purpose of teaching Philosophy in High School. For the realization of this intention, the research was divided into two parts: a theoretical-critical and a practical-propositional one. Initially, a history of official documents is presented, in which the contents of Philosophy were presented as a curricular element and, next, a detail on the method of elaboration of ENEM items. Closing the first part, the “heart” of the research presents a philosophical conception of the teaching of Philosophy: if its teaching is possible, if what is taught are possible “objects” of knowledge (syllabus) or a philosophical posture in face of reality . The most common perspective before the authors used as bibliographic references is that of teaching philosophy based on the historical-thematic-problematizing triad. With regard to ENEM, the process of formulating objective assessment items based on the referential matrices, is a unique condition for the process of systematic and deep reflection, since it is necessary to establish connections between competencies and skills (descriptors) and possible themes and problematizations carried out throughout the history of philosophical thought. It is also proposed an evaluation process in which students analyze the items after their application and that their correction is also an intense moment of apprehension of philosophical concepts. In the second part of the work, there is an analysis of Philosophy items in the 2017 and 2018 editions of ENEM, in an analytical framework in the precursor light of Daniela Comiram, who had done the same analysis with previous editions of the exam. And, finally, items prepared from the National Common Curricular Base are proposed, as a suggestion of teachers in the area of Human Sciences, especially the curricular component of Philosophy.